2020
DOI: 10.1002/dta.2873
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in hematological athlete biological passport biomarkers in relation to the menstrual cycle

Abstract: The interpretation of athlete biological passport (ABP) is strengthened by understanding the natural fluctuations in its biological parameters. Here we have assessed the influence of the menstrual cycle on the hematological module of the ABP. Seventeen women with regular menses were included. Blood samples were collected once a week for two consecutive cycles and analyzed for hematological parameters. Menstrual phases were hormonally determined. The intra‐individual variation in the hematological parameters wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
37
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 35 publications
6
37
1
Order By: Relevance
“…However, as significant interactions of time × treatment were evident for all the hematological analyses, the required power was reached. In addition, we did not control for the menstrual cycle, which may affect reticulocyte percentage, 34 but as we did not observe any effect of sex on the hematological changes, it does not appear to constitute a limitation.…”
Section: Discussionmentioning
confidence: 80%
“…However, as significant interactions of time × treatment were evident for all the hematological analyses, the required power was reached. In addition, we did not control for the menstrual cycle, which may affect reticulocyte percentage, 34 but as we did not observe any effect of sex on the hematological changes, it does not appear to constitute a limitation.…”
Section: Discussionmentioning
confidence: 80%
“…Consequently, a seated position for 5–10 min is recommended to obtain ABP data exempt from activity‐ or supine‐induced plasma volume (PV) shifts 181 . Studies on the potential influence of the menstrual cycle on ABP parameters indicated merely negligible effects 182 ; hyperhydration was shown to have no impact on ABP readings 183 ; and likewise, exercise‐induced sweating dehydration with an average loss of up to 3.1% of body mass was reported to have no effect on [Hb] during ABP testing, 184 demonstrating the robustness of the hematological module. However, dehydration due to medical conditions such as, for example, secretory diarrhea (as simulated by the administration of diuretic drugs) was found to result in highly abnormal ABP profiles and needs consideration in ABP profile interpretations.…”
Section: Manipulation Of Blood and Blood Componentsmentioning
confidence: 99%
“…Consequently, a seated position for 5-10 min is recommended to obtain ABP data exempt from activity-or supine-induced plasma volume (PV) shifts. 181 Studies on the potential influence of the menstrual cycle on ABP parameters indicated merely negligible effects 182 ;…”
Section: Manipulation Of Blood and Blood Componentsmentioning
confidence: 99%
“…The study cohort and sampling are thoroughly described in Mullen et al 14 Briefly, 17 women with regular menses, aged 18-41, participated in the study, and herein, eight of them were included (for demographic information, see Table 1). The women were nonpregnant, did not use any hormonal drugs, and had a body mass index (BMI) < 24.9.…”
Section: Womenmentioning
confidence: 99%
“…Occasionally, intake of painkillers was reported. follicle-stimulating hormone (FSH) were performed as previously described 14 to biologically classify the menstrual phases. (Figure 2A).…”
Section: Womenmentioning
confidence: 99%